Optimizing Water Pressure Control using Proportional-Integral-Derivative (PID) Controller via Variable Frequency Drive (VFD) - PUYKHAMMEE, Vadsana; Thongphanh, Phutsavnh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The challenges of water pressure fluctuations and significant electrical energy loss in pumping systems, driven by dynamic and irregular consumer usage behaviors, present critical issues for water supply management in high-rise buildings. This research aims to investigate and optimize closed-loop water pressure control using a Proportional-Integral-Derivative (PID) controller integrated with a Variable Frequency Drive (VFD) to maintain stable water pressure under highly fluctuating demand conditions. The methodology involves developing a mathematical model based on pump Affinity Laws and simulating the system using MATLAB/Simulink. The system was evaluated by establishing a target pressure set-point of 30.6 meters and introducing flow rate disturbances ranging from 20 to 60 liters per second (L/s). The simulation results demonstrate that the tuned PID controller with parameters , , and responds rapidly to system variations, achieving a settling time of less than 1.5 seconds and successfully eliminating steady-state error with statistical significance ( ). Furthermore, the implementation of the VFD allows for motor frequency reduction during low-demand periods, thereby enhancing energy savings and mitigating the adverse effects of water hammer within the pipeline network. These findings confirm that the developed system possesses high stability and can be effectively utilized as a benchmark for designing smart water supply systems in practical engineering applications.